Contribution of storm time substorms to the prompt electric field disturbances in the equatorial ionosphere. Issue 5 (8th May 2017) - Hui, Debrup; Chakrabarty, D.; Sekar, R.; Reeves, G. D.; Yoshikawa, A.; Shiokawa, K.
Abstract: This study tries to bring out the fact that storm time substorms can compete and at times significantly contribute to the geomagnetically disturbed time prompt penetration electric field effects on low and equatorial latitudes. Observations of unusual equatorial plasma drift data from Jicamarca Unattended Long‐term Investigations of the Ionosphere and Atmosphere during two space weather events show that substorms can induce both eastward and westward penetration electric fields under steady southward interplanetary magnetic field (IMF B z ) conditions. During the first event on 2 January 2005, the enhancement of the daytime eastward electric field over Jicamarca due to substorm is found to be comparable with the Sq and interplanetary electric field (IEFy) generated electric fields combined. During the second event on 19 August 2006, the substorm is seen to weaken the daytime eastward field thereby inducing a westward field in spite of the absence of northward turning of IMF B z (overshielding). The westward electric field perturbation in the absence of any overshielding events is observationally sparse and contrary to the earlier results. Further, the substorm‐induced field is found to be strong enough to compete or almost nullify the effects of storm time IEFy fields. This study also shows quantitatively that at times substorm contribution to the disturbed time prompt electric fields can be significant and thus should be taken into consideration in evaluating penetration events over low latitudes. Key Points: Unusually large storm time plasma drifts are observed by JULIA despite small IEFy magnitudes Substorms at times can contribute significantly to the disturbed time electric field in equatorial ionosphere Substorms induce both eastward and westward electric fields over equatorial latitudes